Find the real solution(s) of the given equation. \( (-7 x-1)^{2}-(-7 x-1)-2=0 \) Give exact answers using fractions and square roots, not de
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
Let’s simplify the equation by letting \( y = -7x - 1 \). This transforms our equation into: \[ y^2 - y - 2 = 0 \] Now, we can factor this quadratic: \[ (y - 2)(y + 1) = 0 \] Setting each factor equal to zero gives us: \[ y - 2 = 0 \quad \Rightarrow \quad y = 2 \] \[ y + 1 = 0 \quad \Rightarrow \quad y = -1 \] Now, we substitute back \( y = -7x - 1 \): 1. For \( y = 2 \): \[ -7x - 1 = 2 \quad \Rightarrow \quad -7x = 3 \quad \Rightarrow \quad x = -\frac{3}{7} \] 2. For \( y = -1 \): \[ -7x - 1 = -1 \quad \Rightarrow \quad -7x = 0 \quad \Rightarrow \quad x = 0 \] Thus, the real solutions are: \[ x = -\frac{3}{7} \quad \text{and} \quad x = 0 \]